Fellow tribesmen : the image of native Americans, national identity, and Nazi ideology in Germany - Usbeck, Frank (Studies in German history ;, 2015)
"Throughout the 19th and 20th centuries, Germans exhibited a widespread cultural passion for tales and representations of Native Americans. This book explores the evolution of German national identity and its relationship with the ideas and cultural practices around 'Indianthusiasm.' Pervasive and adaptable, imagery of Native Americans was appropriated by Nazi propaganda and merged with exceptionalist notions of German tribalism, oxymoronically promoting the Nazis' racial ideology. This book combines cultural and intellectual history to scrutinize the motifs of Native American imagery in German literature, media, and scholarship, and analyzes how these motifs facilitated the propaganda effort to nurture national pride, racial thought, militarism, and hatred against the Allied powers among the German populace"--Provided by publisher